Escape From Iran The Exodus of Persian Jewry During the Islamic Revolution of 1979. - Hecht. (G&D Media, 2020)
This is the story of the dramatic rescue and emigration of thousands of Iranian Jewish students to America, and the miraculous rebirth of an ancient civilization in a brand new world.